Pioneering death : the violence of boyhood in turn-of-the-century Oregon - Boag, Peter, 1961- (Emil and Kathleen Sick lecture-book series in western history and biography., 2022)
"In rural Oregon in 1895, an 18-year-old youth named Loyd Montgomery murdered his parents and a visiting neighbor and was then tried and executed for the crime. Placing these killings within the broader context of the agrarian crisis and the demise of the Oregon pioneer generation, Boag illuminates not only why the parricide happened but also the effects it had on the community and society wherein it occurred. More than a local history, this project examines larger issues of regional and U.S. history of the era: boyhood in the late 19th century, the economic and political woes of farmers in Oregon and the Northwest in the face of globalization and industrialization, and challenges to the cultural and social ideals of rural Oregon and the U.S. in general. Boag also critically examines the ways in which white community members integrated the murders into their local histories to construct narratives of peace, progress, and justice in order to preserve the idyllic myth of the Pacific Northwest at the turn of the century"--